From Local to Global: Examining Sister City Cooperation as Paradiplomacy Practice in Denpasar City, Bali, Indonesia (Jurnal Bina Praja, 2021)
This research aims to examine the sister city cooperation as paradiplomacy practice to establish international relations in Denpasar City, Bali, Indonesia, through the multidisciplinary perspectives of Legal and International Relations studies. This research seeks to answer how Denpasar City, Bali conducts its paradiplomacy through sister cities to build international cooperation and the legal and social challenges. The implementation of three layers of paradiplomacy, according to Lecours (2008), which consists of the economic issue (first layer), cultural, educational, technological, and other multidimensional aspects (second layer), and political considerations (third layer), will be determined by using interview methods and International Relations literature studies. The legal corridor of conducting paradiplomacy, as it assesses the legal basis and limitation for local government to interact with international actors, will be explored using the data collected through legal instruments and legal literature studies. The research used a qualitative empirical approach to connect both disciplines. The results show that Denpasar’s sister city cooperation can be classified as the first layer (economy) and the second layer (culture, education, and technology) of paradiplomacy practice, whereas the third layer (politics) is excluded from this cooperation. Denpasar faces several challenges in conducting its sister city plans of action, such as legal obstacles, continuity of the cooperation, human resources limitation, funding reallocation, and limited citizen participation. The COVID-19 pandemic affects the implementation of the planned sister city cooperation.
Keywords: Denpasar City; international law; international relations; paradiplomacy; sister city